Familiarity of Online Learning Platform in Catching Up the Academic Accomplishment in East Kalimantan Sport School - Khusnul Khatimah; Yeni Rahmawati; Abdul Halim (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2021)
Learning  media  is  increasingly  varied  along  with  the  rapid  of  technological advances.  The  method  uses  a  lot  of  various  media  to  improve  the  quality  of learning outcomes. The object of this study was to identify the usage of online learning based to increase students’ interest in learning among students in Sport School East Kalimantan. The total populations of this research were 423 students. By using Slovin formula, it was obtained as many as 205 students. The data collection method in the form was an online questionnaire as research’s instrument. The questionnaire was sent by researchers and asked a help from SKOI teacher who become intermediaries as well. For administrative purposes in the process of data collection and data processing, Due to the COVID-19 pandemic conditions, some SKOI  students who  randomly  selected were  out  of  town  causing  the filling  of questionnaire run slowly. In the middle of 2020, data processing was carried out. It was stated that the data were normally distributed (pre-test and post-test data). By using Kolmogorov Smirnov test with a significant level of .000 with a correlation test level of .090 (indicating that the data has a high correlation), the data entered was significant, namely that the use of the Google suite for learning English was very significant